Analisis Sentimen Tingkat Perbandingan Efisen antara Kendaraan BBM denganKendaraan Listrik Menggunakan Algoritma Naives Bayes - Arvin Rafialdo; Achmad Ramadhan; Ananda Prasta Warasati Janah; Azhar Haikal Anwar; Firman Noor Hasan (Fakultas Teknik, Universitas Muhammadiyah Prof. Dr. Hamka, Jakarta, 2022)
The most widely used energy sources today are fossil fuels, one of which is oil, especially Indonesia isstill very dependent on fossil energy, almost 95% of Indonesia's energy needs are still supplied by fossils.Along with the times, many studies are trying to find alternative energy sources, one of which is electric vehicles, as an alternative to the use of fossil energy. Therefore, researchers classify public sentiment and understanding of fuel-oil and electric vehicles using the Naïve Bayes method to compare vehicle efficiency levels. Based on the results of the study, it was found that oil-fueled vehicles with electricity using the Naïve Bayes method yielded 50 results for each data. Fuel-fueled vehicles give positive and negative results, namely 30 and 20. Meanwhile, electric vehicles give positive and negative results of 43 and 7. It can be concluded that public sentiment towards electric vehicles is more efficient than oilfueledvehicles.